Plants are Renewable Source of Medicine and Nanoparticles: A Review - Sreekumar, S.; Nisha, N. C. (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
Plants have been used as a therapeutic agent since time immemorial and its mode of usages have been coevolved with human civilization. Man identified therapeutic potential of plants through trial and error method and passed the knowledge from generation to generation verbally and practice. Before 16th century plant or plant parts have been used as such and in between 16th and 18th century mixture of plant or plant parts were used as medicine. Since in the beginning of 18th century pure compounds have been isolated from plants and used as medicine. Today over 6,00,000 plant derived compounds are isolated from various plants and out of 252 drugs considered as basic and essential by the World Health Organization (WHO), 11% are exclusively of plant origin and a significant number are synthetic drugs obtained from natural precursors. The plant derived drugs are found to be more stable, induce fewer side effects and showed pleotropic druggability due to the unprecedented structural features and functional diversity. Moreover, plant derived molecules are synthesized within the living system and repeatedly tested and modified through long term evolutionary process. In addition to phytomolecules, plants are also the best synthesizer of nanoparticles with diverse therapeutic activities. The herbal medicines or the plant extracts contains a plethora of chemical constituents and numerous functional groups such as C=C – alkenyl, C=N – amide, O=H – phenolic and alcohol, N=H – amine, C-H and COO- carboxylic acid etc., these functional group may bind with metal ions and form nanoparticles. Biosynthesis of different metal nanoparticles such as Cu, Co, Ag, Au, Pd, Pt, Zn, Mn, Ti, Ni, Fe, etc. and alloy of Au, Al, Zn were successfully achieved. The versatility of plant derived drugs under various aspects such as historic background, plant derived drugs in modern medicine, importance of medicinal plants in drug discovery, plant derived drugs - advantages and disadvantages, characteristic features of plant derived drugs, major challenges in plant derived drug discovery, value and market potential, approaches of drug discovery from plants, importance of phytochemical and pharmacological screening, drug discovery from plants – Indian scenario, plant derived nano medicine are briefly reviewed.